Blood–brain barrier permeable nano immunoconjugates induce local immune responses for glioma therapy - Anna Galstyan (Nature Portfolio, 2019)
Glioma therapy with checkpoint inhibitors has limited blood–brain barrier (BBB) penetration and therapeutic effects. Here, the authors develop nanopolymer-conjugated checkpoint inhibitors and show their trans-BBB delivery and anti-glioma efficacy.